AN ANALYSIS OF TRADITIONAL TATTOO (LUNAT) USED BY PEOPLE IN BAUS VILLAGE, BOKING DISTRICT SOUTH CENTRAL TIMOR REGENCY (A SEMIOTICS STUDY) - Nancy K. Leokoy (Academic Journal of Educational Sciences, 2018)
2015. An Analysis of Traditional Tattoo (Lunat) Used By People In Baus Village, Boking District, South Central Timor Regency (A Semiotics Study), English Study Program, Faculty of Teacher Training and Educational Science, Nusa Cendana Univeristy. Supervisors: (I) Dr.Agustinus Semiun, MA (II) Dra. Hilda Nalley, M.Ed. This research was conducted to answer the following problems : (1) What are the motifs of traditional tattoo (lunat) used by the people in Baus village, Boking District, South Central Timor Regency? (2) What are the meanings of the motifs of traditional tattoo (lunat) used by the people in Baus village, Boking District, South Central Timor Regency? (3) What are the functions of traditional tattoo (lunat) used by the people in Baus village,Boking District, South Central Timor Regency?. The aims of this research are to find out and analyze the motifs, meanings and functions of traditional tattoo (lunat) used by the people in Baus village, Boking District, South Central Timor Regency. The method used to collect the data was descriptive qualitative method. In gathering the data, the researcher applied observation and interview to seven people who have traditional tattoo (lunat) as the informants. Techniques of data collection applied in this research were note taking, recording and documentation. In analyzing the data, the researcher took the picture (photo) of lunats from the informants who have lunat on their body. Then, the researcher analyzed the motifs, meanings and functions of lunats based on the semiotics perspective and cultural point of view of people in Baus village. The result of research showed that traditional tattoo (lunat) used by people in Baus Village consist of seven motifs with their meaning. Lunat kanaf (tattoo of name) used to show someone’s identity. Lunat nekaf (tattoo of love) revealed someone’s feeling. Lunat bik lusu (tattoo of lizard) as the reminder and the message bearer for them. Lunat kolo (tattoo of bird) told people that the time to plant is coming. Lunat teke (tattoo of gecko) told about the change of new month. Lunat nape (tattoo of butterfly) symbolized the process of human life. Lunat pika bu’uf (tattoo of plate’s bottom) became a commemoration that Japan ever colonized Indonesia. Meanwhile, there were some functions of lunats such as aesthetic function to express their art skill especially in drawing a design. In social view, by making lunat people can keep their fraternity. Dealing with historical function, lunat becomes a medium for people in Baus Village to immortalize Japanese colonialism as a history for the next generation.